THE ROLE AND EFFECTIVENESS OF VOCATIONAL EDUCATION POLICY IN IMPROVING LANGUAGE COMPETENCE AND COMPETITIVENESS OF VOCATIONAL HIGH SCHOOL GRADUATES - Nur Kholis Usman; Yuliani; Mi'at; Khairul Efendi; Ahmad Suriansyah; Ratna Purwanti (Universitas PGRI Palembang, 2025)
Vocational education plays a pivotal role in enhancing the competitiveness of Vocational High School (SMK) graduates in the face of global demands. This study explores the role and effectiveness of vocational education policies in improving language competence and graduate employability at SMKN 1 Telagasari. Employing a case study approach, the findings reveal that policies encouraging collaboration between schools and industry, along with the adoption of competency-based curricula, significantly support the development of both technical skills and language-related soft skills. The results show a marked improvement in graduate employability following the implementation of these policies. However, the study also identifies challenges such as regional disparities in vocational education quality and limited funding and infrastructure. Strengthening policy support and increasing resource allocation are essential to improving vocational education outcomes at a national level.